A feasibility study on the adaptation of the eRizal Program at the Little Shepherd Integrated Montessori - Little Shepherd Business and Science High School - Ragaza, Merceidez Louise S. (2012)
The eRizal program is the Philippines' premier project in realizing the vision of a bookless society through the Rizal Tablets, a seven inch touchscreen computer device aimed to complement/supplement, and later on, replace print textbooks at the different national high schools in Laguna. Upon its implementation and seeming success, private schools will need to consider adapting the eRizal program or develop a similar program to provide the best services in line with their mission, vision, goals, and objectives. In determining the operational, technical, economic, and schedule feasibility of adapting the project, the study focuses at the Little Shepherd Business and Science High School (LSBSHS), due to its proximity to the schools affected by the eRizal program, with four tablet candidates i.e. (1) Rizal Tablet, (2) Apple's iPad 2, (3) Samsung Galaxy Tab 7.0 Plus, and (4) Amazon's Kindle Fire.